Difficulty Factors for Fourth Grade Students in Thematic Learning - Susilo, Bening Prameswari (Universitas Pendidikan Ganesha, 2022)
Obstacles found during this learning process can come from the teacher, the school environment, or the students themselves. This study aims to analyze the factors that cause students to have learning difficulties. This research uses descriptive qualitative research. The subjects of this study were one principal, two teachers, and 20 students. This research uses interview, observation, and documentation data collection techniques. Data collection methods are data reduction, data presentation, and conclusion drawing. The study results are the difficulty factors experienced by students come from within and outside the students themselves. Inside students include the enthusiasm and interest of students in learning, student intelligence, student body, and mental conditions. From outside the students themselves, namely the student's environmental conditions, relationships with friends, parents, and teachers, classroom conditions, advice and infrastructure, learning media, and difficulties in learning materials. Two factors that cause students to experience learning difficulties greatly influence student learning success. Students who are in elementary school have not been able to overcome the problems experienced, therefore students need to get more attention from teachers and parents to overcome the learning difficulties they are experiencing.